COMPARISON OF BODY IMAGE LEVELS OF STUDENTS WHO DO SPORTS AND WHO DO NOT DO SPORTS - ATAR, Özdemir (IJRDO- Journal of Educational Research, 2017)
The purpose of this study is to compare body image levels of students who do sports and who do not do sports. Population of the study was constituted by students studying at Istanbul Gelişim University whereas the sample was represented by 81 students studying at Istanbul Gelişim University School of Physical Education and Sports and 80 students studying Architecture, Psychology and Sociology who voluntarily participated in our study. Body Appreciation Scale, validity and reliability study of which was conducted by Anlı et al. in 2015, was used as data collection tool. For analyzing data obtained, SPSS 20 was used. Single sample “Kolmogorov-Smirnov” test was applied to learn whether the data had a normal distribution while “Anova-Homogenety of variance” test was applied to determine its homogeneity and it was seen that the data was homogeneous, with a normal distribution. In analysis of data, descriptive statistics and independent sample t- test were applied. It was found as a result of the study that body appreciation scores of people who do do sports regularly were higher than those of who do not do sports regularly.